Transformation and connection: the stories of four young women attending an alternative high school - Newman-Gonchar, Rebecca A., author; Banning, James, advisor; Deniston, Terry, advisor; Cross, Jennifer, committee member; Lehmann, Jean P., committee member (Colorado State University. Libraries, 2005)
This dissertation tells the story of the author's oral defense. It is written from the perspective of the author, as she experiences her defense, watches her participants tell their stories, and converses with her committee. To do narrative inquiry, the author had to write an encompassing story. She could not rely on strict academic form and structure and continue to assert that people learn best through stories and through the experience of hearing another's perspective. She had to write and teach how she believes people learn best, through story. This story explored the authors' research on the experiences and stories of four young women who attended an alternative high school. Each young woman in the study had once been enrolled in a traditional high school and then chose to attend the alternative high school. The goal of the study was to understand how each young woman made sense of her experiences of disconnection from the traditional high school and reconnection to the alternative high school through story-telling and to explore how each made sense of her personal transformation. Semi-structured, participant-led interviews were employed to uncover stories of transformation, connection, and sociological implications of their educational experiences. The stories told by the four women who participated in this study revealed the complexity of their experiences. When heard fully without the label "at-risk," these young women's stories revealed far more complex stories and sense-making than could otherwise be explored. The four young women transformed their lives, were supported in that transformation inside the alternative school setting, and felt connected to their education and their educational community in the alternative school. These stories depict success for the young women who transformed their lives and connected to their education and for the educational system that provided them that opportunity. This research also explored implications for narrative qualitative research. Topics include intersubjectivity, participant participation, idiosyncrasies that inhibit an exact practice, and parallel story telling.
Keywords: secondary education; educational sociology